Remote Sensing Assessment of Tourism's Groundwater Consumption: Evapotranspiration Analysis in the Northern Piedmont of the Western High Atlas, Morocco - Hamza Ait Zamzami; Mohammed Elaanzouli; Ayoub ZAHRANI; Oumaima Boumeaza; Brahim Aachrine; Jamila Saidi; Muhammad Musiyam; Taieb Boumeaza (Forum Geografi, 2025)
In semi-arid regions facing escalating water scarcity, tourism development poses critical risks to groundwater sustainability. This study examines the exploitation of groundwater resources by tourism infrastructure in the northern piedmont of Morocco’s Western High Atlas, aiming to quantify withdrawals and assess their long-term viability. By integrating satellite-derived evapotranspiration (WaPOR) and precipitation (CHIRPS) data with field surveys of tourism investments, we analyzed irrigation water demand relative to agronomic requirements and mapped spatial exploitation patterns. Results indicate that 65% of tourism establishments exceed sustainable groundwater use for irrigation by 25–30%, with overexploitation concentrated in communes where tourism development is most intensive. These practices threaten local ecosystems, reduce agricultural productivity, and compromise domestic water security. Our findings highlight the urgent need for enforcing groundwater extraction regulations, adopting water-efficient irrigation systems, and developing alternative water sources to reconcile regional economic growth with the preservation of critical groundwater resources in water-stressed environments.